ASR, Volume 24, n° 1, 2020 - Full Issue - system, journal (African Sociological Review, 2021)
Contents Editorial .................................................................1 General Issue Reconnecting African Sociology to the Mother: Towards a Woman-centred Endogenous Sociology in South Africa Babalwa Magoqwana & Jimi Adesina .................................................4 Developpement, Conditions Sociales et Sante de la Population en Afrique Sub-Saharienne Jacquineau Azétsop .............................................25 Research Papers An Overview of the Conditions of Workers and Unions in South Africa and Nigeria Ifeanyi P. Onyeonoru & Mondli Hlatshwayo ...............................51 Ex-Mineworkers and New Skills: Contradictory Perspectives of Stakeholders Siphelo Ngcwangu ................................................77 Perception du Centre d’Observation des Minuers (COM) d’Abidjan par les Minuers Incaceres et Persistance dans les actes Antisociaux Jean Louis Niamke & Marie-Thérèse Dahonnon Zeze ..............................103 L’émergence et les perceptions des risques socio-environnementaux liés aux pratiques ďassainissement et aux usages de ĺeau sur la lagune Aghien en Côte ďIvoire Chrislain Ahi Kouadio, Veronica Mitroi, José-Frédéric Deroubaix & Ibo Jonas ................................119 Symbolic violence, academic capital and reflexivity: A case-study of post-apartheid curriculum change for teacher education using Bourdieu Wayne Dirk ........................................................145 Environnement socio-culturel et sous représentativité des femmes 170 dans les programmes de lutte contre le travail des enfants dans le secteur du cacao en Côte ďIvoire. Kouassi Kouman Vincent Mouroufie, Oleh Kam & Moussa Sangare .........................170 Enjeux du conflit humains- hippopotames au lac Ezanga (Lambaréné-Gabon) Jean-Emery Etoughé-Efé ....................................184 The nexus of decision making, re-allocation and migration on Children orphaned and affected by HIV and AIDS: a case study of rural Lesotho Josphine Hapazari .....................................................212 Generational Variations in Purpose of Childbearing among Ever-Married Women and Implications for Contraceptive Behaviour in Idanre Town Ondo State Onipede Wusu, Olabusoye Olu Oguntola-Laguda,Deborah Onyinye Charles, Kazeem Olayinka Sokoya, Augustus Andikan Umana, Whitney Adesuwa Esemetoye, Abiola Tomiwa Oluwabi, Odunayo Bonu,Shuaib Olamilekan Kazeem, Omobolanle Nimota Abass, Olamide Geminat Ojikutu, Rafiat Olabisi Azeez, Oluwadamilola Ayomide Ismail & Ibrahim Olayinka Alogba ......................................233 Book Review Handbook on Society and Social Policy 248 By Nick Ellison and Tina Haux (Eds.) Olajide Oloyede ...............248